Intervención en crisis: Análisis de los procesos de comunicación entre médicos, enfermeras, personal auxiliar de enfermería, pacientes del servicio de recuperación y sus familiares del Hospital Carlos Andrade Marín - Sambachi Sánchez, María Elena (2013)
The next document presents the intervention in the Recovery Area of Hospital Carlos Andrade Marin´s communication process, using information recollected to doctors, nurses, complementary personal, patients and their families. The most commons signs of patients in the hospital´s recovery area are the anxiety caused because of knowing the results of their surgical operations and their diagnosis. That is why is important to know that the patients in this kind of areas are not alone because their relatives demand constant, complete and good information about the health´s state of the people they love and the possibilities of keep in touch with them every time they could. In the first place we studied the system, after that we studied some theories like communication respect and crisis´s interventions and how it could become a priceless strategy in order to improve the patients´ attention in the hospital.